“On Their Knees”: Politics, Protest, and the Cancellation of the Pickering Airport, 1972–1975 - Rowan, Michael (Urban History Review / Revue d'histoire urbaine, 2017)
The Pickering Airport in Ontario was announced in March 1972 and cancelled in September 1975. During that three-year period there was a bitter struggle between protesters, whose land was expropriated for the airport, and the federal government. The expropriation process gave both protesters and bureaucrats the opportunity to plead their cases through public forums on why the Pickering Airport was necessary or not. By the 1970s, citizens became more distrustful of experts and believed they deserved a full seat at the policy table, while bureaucrats were frustrated by challenges to their authority and the slow policy process. The debate over the Pickering Airport raises important questions about the effectiveness of public forums like hearings or public inquires in determining policy. Citizens groups may have a seat at the policy table, but the policy process has remained bitter and divisive.